2018
DOI: 10.1037/adb0000395
|View full text |Cite
|
Sign up to set email alerts
|

Solitary gambling mediates the risk pathway from anxiety sensitivity to excessive gambling: Evidence from a longitudinal ecological momentary assessment study.

Abstract: Anxiety and gambling problems co-occur at high rates. Social learning theory (SLT) suggests that people high in anxiety engage in excessive gambling to reduce negative affect. Because anxiety sensitivity (AS) is a vulnerability factor associated with addictive behaviors, it is important to identify mediators in this high-risk pathway. Emerging research shows that social context mediates associations between anxiety vulnerability and addictive behaviors. This literature shows that anxiety-prone people are at in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 60 publications
(87 reference statements)
0
5
0
4
Order By: Relevance
“…Similarly, in an Australian-based sample, 31.5% of sports bettors reported watching sport alone (Hing, Lamont, Vitartas, & Fink, 2015b). The combination of solitude and gambling can be problematic, as many anxiety-coping gambling habits derive from solitary gambling (Bristow et al, 2018).…”
Section: The Singularities Of In-play Bettingmentioning
confidence: 99%
“…Similarly, in an Australian-based sample, 31.5% of sports bettors reported watching sport alone (Hing, Lamont, Vitartas, & Fink, 2015b). The combination of solitude and gambling can be problematic, as many anxiety-coping gambling habits derive from solitary gambling (Bristow et al, 2018).…”
Section: The Singularities Of In-play Bettingmentioning
confidence: 99%
“…Individuals with higher levels of well-being are more likely to engage in emotion regulatory strategies, such as reappraisal (Banyard et al, 2017;Gross & John, 2003), and have more positive appraisals regarding their life circumstances (Diener, 2009). In contrast, lower levels of well-being are associated with maladaptive cognitions and coping styles (KL et al, 2017), which may lead some people to gamble in an effort to distract themselves from distressing emotions (Blaszczynski & Nower, 2002;Bristow et al, 2018;Moon et al, 2017). Researchers have consistently demonstrated that greater levels of wellbeing protect individuals from experiencing ACE-related harms (e.g., poor psychological and physical health) after a history of childhood adversity (Baiden et al, 2016;Banyard et al, 2017;Crandall et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In line with these findings about interpersonal conflicts, almost-exclusively-online gamblers did not have higher levels of social anxiety disorder than offline gamblers, whereas mixed gamblers did. This is particularly remarkable because one might expect individuals with higher levels of social anxiety disorder to tend to engage in solitary gambling activities online ( 41 ). However, based on our data, it could be hypothesised that mixed gamblers more often encounter interpersonal conflict, leading to greater feelings of shame in social interactions and thus symptoms of social anxiety disorder, whereas almost-exclusively-online gamblers report less interpersonal conflict and fewer symptoms of social anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%